SIKAP PETANI HORTIKULTURA SAYUR TERHADAP PERAN PENYULUH PERTANIAN DALAM PEMBERDAYAAN PETANI DI DESA LEWOKELENG KECAMATAN ILE BOLENG KABUPATEN FLORES TIMUR - Marselina Kewa Kian; Mustafa Abdurrachman; Ignatius Sinu (Buletin Ilmiah Impas, 2022)
The study has been carried out in the village of lewokeleng , Ile boleng district, east Flores regency in December through January 2021. This research was intended to know; 1) knowing the role of agriculture in the rural empowerment of farmers in the village of lewokeleng, Ile boleng sub district, east flores regency 2) know the farmers’ attitude toward the development of agriculture in the village of lewokeleng, Ileboleng sub district, east Flores regency. The identification of this study was done intentionally on the basis of consideration that it was one of the central areas of vegetable production. The population in this study included all the vegetable farmers in the village of lewokeleng of 50 families. Everything’s set to sample. To know the first purpose of the data being analysed quantitatively and to know the purpose to both data was elaborately analysed using the likert scale. The results of the data analysis show that :1) the role of guiding agriculture is consistent with the empowerment of farmers in the village of lewokeleng. The role of farmers in agricultural development has 5 elements, which are related to the vegetable horticultural farm, whichis as communitators, innovators, educaters, facilitators and motivators. 2) the development of farmers in the rural community of lewokeleng has been uncertain about how the average score of 34.24 % rests on the 25-34 range. This shows that the instructors at the research site have performed their roles properly as communicators, educators, innovators, facilitators and multivators in the increased horticulture of vegetables but have not yet been done optimally.